Retention of placenta and its associated factors in Bangladeshi zebu cattle (Bangladesh Veterinarian, 2022)
The aim was to find out the incidence of retention of placenta in 175 zebu cattle with regard to age, body condition score (BCS), parity, and feeding system. Pretested questionnaire was used for collecting the information. The overall incidence of manually removed placenta was 10.3%. Age, body condition score and feeding system had significant effect (P